Oncolytic reovirus in combination with chemotherapy in metastatic or recurrent non–small cell lung cancer patients with KRAS‐activated tumors. Issue 6 (28th December 2015) - Villalona‐Calero, Miguel A.; Lam, Elaine; Otterson, Gregory A.; Zhao, Weiqiang; Timmons, Matthew; Subramaniam, Deepa; Hade, Erinn M.; Gill, George M.; Coffey, Matthew; Selvaggi, Giovanni; Bertino, Erin; Chao, Bo; et al.
Abstract : BACKGROUND: The type 3 Dearing reovirus (Reolysin) is a naturally occurring virus that preferentially infects and causes oncolysis in tumor cells with a Ras ‐activated pathway. It induces host immunity and cell cycle arrest and acts synergistically with cytotoxic agents. METHODS: This study evaluated Reolysin combined with paclitaxel and carboplatin in patients with metastatic/recurrent KRAS‐mutated or epidermal growth factor receptor (EGFR)–mutated/amplified non–small cell lung cancer. RESULTS: Thirty‐seven patients were treated. Molecular alterations included 20 KRAS mutations, 10 EGFR amplifications, 3 EGFR mutations, and 4 BRAF‐V600E mutations. In total, 242 cycles (median, 4; range, 1‐47) were completed. The initial doses were area under the curve (AUC) 6 mg/mL/min for carboplatin, 200 mg/m 2 for paclitaxel on day 1, and 3 × 10 10 50% tissue culture infective dose for Reolysin on days 1 to 5 of each 21‐day cycle. Because of diarrhea and febrile neutropenia (in the first 2 patients), subsequent doses were reduced to 175 mg/m 2 for paclitaxel and AUC 5 mg/mL/min for carboplatin. Toxicities included fatigue, diarrhea, nausea/vomiting, neutropenia, arthralgia/myalgia, anorexia, and electrolyte abnormalities. Response Evaluation Criteria in Solid Tumors 1.0 responses included the following: partial response for 11 patients, stable disease (SD) for 20 patients, progressive disease for 4 patients, and not evaluable for 2 patients (objective response rate, 31%; 90% 1‐sided lower confidence interval, 21%). Four SD patients had >40% positron emission tomography standardized uptake value reductions. The median progression‐free survival, median overall survival, and 12‐month overall survival rate were 4 months, 13.1 months, and 57%, respectively. Seven patients were alive after a median follow‐up of 34.2 months; they included 2 patients without disease progression at 37 and 50 months. CONCLUSIONS: Reolysin in combination with paclitaxel and carboplatin was well tolerated. The observed response rate suggests a benefit of the reovirus for chemotherapy. A follow‐up randomized study is recommended. The proportion of patients surviving longer than 2 years (30%) suggests a second/third‐line treatment effect or possibly the triggering of an immune response after tumor reovirus infiltration. Cancer 2016;122:875–83 . © 2015 American Cancer Society . Abstract : The naturally occurring oncolytic reovirus Reolysin, which preferentially targets KRAS‐activated cancer cells, is reasonably well tolerated in combination with chemotherapy in lung cancer patients with activated KRAS. The clinical outcomes observed are encouraging in this patient population, and a subsequent randomized trial is planned.